Induction of lead-binding phytochelatins in vetiver grass [vetiveria zizanioides (L.)] - Andra, Syam S.; Datta, Rupali K.; Sarkar, Dibyendu; Makris, Konstantinos C.; Mullens, Conor P.; Sahi, Shivendra Vikram; Bach, Stephan B H (My University, 2009)
Elevated lead (Pb) concentrations in residential houseyards around house walls painted with Pb-based pigments pose serious human health risks, especially to children. Vetiver grass (Vetiveria zizanioides L.) has shown promise for use in in situ Pb phytoremediation efforts. However, little is known about the biochemical mechanisms responsible for the observed high Pb tolerance by vetiver. We hypothesized that vetiver exposure to Pb induced the synthesis of phytochelatins (PCn) and the formation of Pb-PCn complexes, alleviating the phytotoxic effects of free Pb ions. Our main objective was to identify PCn and Pb-PCn complexes in root and shoot compartments of vetiver grass using high-performance liquid chromatography coupled to electrospray mass spectrometry (HPLC-ES-MS). After 7 d of exposure to Pb, vetiver accumulated up to 3000 mg Pb kg-1 in shoot tissues, but much higher Pb concentrations were measured in root (∼20,000 mg kg-1), without phytotoxic symptoms. Scanning electron micrographs showed Pb deposition in the vascular tissues of root and shoot, suggesting Pb translocation to shoot. Collision-induced dissociation analyses in MS/ MS mode during HPLC-ES-MS analysis allowed for the confirmation of four unique PCn (n = 1-4) based on their respective amino acid sequence. The high tolerance of vetiver grass to Pb was attributed to the formation of PCn and Pb-PCn complexes within the plant tissues, using ES-MS and Pb mass isotopic patterns. These data illustrate the mechanism of high Pb tolerance by vetiver grass, suggesting its potential usefulness for the remediation of Pb-contaminated residential sites. Copyright © 2009 by the American Society of Agronomy, Crop Science Society of America, and Soil Science Society of America.
Keywords: Amino acid sequence; Biochemical mechanisms; Collision-induced dissociation; Electrospray mass spectrometry; Human health risks; In-situ; Isotopic pattern; Pb concentration; Pb ions; Pb tolerance; Phytochelatins; Phytoremediation; Phytotoxic effects; Plant tissues; Residential site; Scanning electron micrographs; Shoot tissue; Vascular tissue; Vetiver grass; Vetiveria zizanioides; Vetiveria zizanioides (L.)